Influence of Carbon Dioxide Temperature on Sprayability and Solubility in Cryogenic Minimum Quantity Lubrication with Bio-Based Lubricants - Meier, Trixi; Lermer, Michael; Gross, Daniel; Hanenkamp, Nico (Manufacturing Driving Circular Economy. GCSM 2022, 2023)
Cryogenic minimum quantity lubrication (CMQL) represents a compromise satisfying both efficiency and sustainability in many manufacturing processes. In previous series of experiments a variation of the thermodynamic state of the cryogenic medium taken from riser bottles could be observed. Consequently, the aim of this study was to specifically control the thermodynamic state of the CO2 and, associated with this, the density after removal from the riser bottles. To achieve this objective conventional cooling was implemented for the CO2 after withdrawal from the riser bundle in order to have a constant liquid state of the CO2 during feeding. The density of the cryogenic medium could be raised from ρ = 550 kg/m3 to over 800 kg/m at a mass flow rate of m˙ CO2 = 5 kg/h with the applied cooling method and can also be stabilized regarding the density pulsation. Subsequently, the effects of temperature-controlled CO2 on the sprayability and solubility in CMQL were examined and resulted in increased atomization of the oils and widening of the spray corridor with a greater main spray length and intensity. In addition stable conditions for the CMQL-supply to the manufacturing process were achieved by a lower pulsation of the CO2-oil mixture.
Keywords: CMQL; Liquid carbon dioxide; Bio-based lubricants